RELIGIOUS DISCRIMINATION PRAXIS IN PUBLIC SCHOOLS IN EAST LOMBOK - Zuarnum, Linda Sari; Hamdi, Saipul (UIN Sunan Kalijaga Yogyakarta, 2022)
AbstractThis article is examining the practice of mono-religious teaching in public school and its influence on students' religious life which tends to mire on exclusive practice in East Lombok. The practice of mono-religious teaching in public schools not merely embark compulsion and religious exclusivity but also create discrimination towards other students for the tendency of applying only one religious practice at school. The impact of the religious praxis in public schools is the force and confinement on the students. Simultaneously, the government keeps producing sharia-based laws that stand for majority notwithstanding the laws fully beneficial for the majority group. Yet the disadvantages for minorities from the laws are obvious. The method used for this research is a qualitative method, the data are collected by interviewing some students from junior public school in East Lombok. There are 10 informants from 4 public schools at the central city of East Lombok, students interviewed are from different gender and religious backgrounds and questioned about their religious experiences at schools. This article comes up with the argument that religious education policy in Indonesia focuses on mono religious study with a vision to build students good morality through religion, however the result of this system is creating the tendency of exclusivity among majority students and restriction for minority students in public school. Mono-religious study and its practice at public schools somehow exceeds religious practice in religious schools and this creates school rules that force students to implement religious activity which is irrelevant with the principal of the public school. And generally, the facility for religious activities only accommodates students who are affiliated with majority belief. The problems that the mono-religious system causes discrimination towards minorities regarding the right for religious activities at public school. The conclusion will be served together with the critique towards the impact of mono-religious teaching in Public School. Keyword: Discrimination, mono-religious teaching, Islamization, public school, East Lombok AbstrakArtikel ini mengkaji praktik pengajaran mono-religious di sekolah umum dan pengaruhnya terhadap kehidupan beragama siswa yang cenderung eksklusif di Lombok Timur. Praktik pengajaran mono-agama di sekolah umum tidak hanya menimbulkan pemaksaan dan eksklusivitas agama, tetapi juga menimbulkan diskriminasi terhadap siswa lain karena adanya kecenderungan hanya menerapkan satu praktik agama di sekolah. Dampak dari praktek keagamaan di sekolah umum adalah timbulnya pemaksaan dan pembatasan terhadap siswa. Bersamaan dengan itu, pemerintah terus memproduksi undang-undang berbasis syariah yang berpihak pada mayoritas meskipun undang-undang tersebut sepenuhnya bermanfaat bagi kelompok mayoritas. Namun kerugian bagi minoritas dari sisi hukum sudah jelas. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, data dikumpulkan dengan cara mewawancarai beberapa siswa SMP Negeri di Lombok Timur. Dalam penelitian ini wawancara dilakukan pada 10 orang informan dari 4 sekolah negeri di pusat kota Lombok Timur, siswa yang diwawancarai berasal dari latar belakang gender dan agama yang berbeda dan ditanyai tentang pengalaman keagamaan mereka di sekolah. Pembahasan dalam artikel ini antara lain: Kebijakan pendidikan agama di Indonesia yang menitikberatkan pada studi mono-religius dengan visi membangun akhlak siswa yang baik melalui praktek keagamaan menimbulkan kecenderungan eksklusivitas di kalangan siswa mayoritas dan pembatasan terhadap siswa minoritas di sekolah negeri. Pembelajaran mono-religious dan praktiknya di sekolah negeri melampaui praktik keagamaan di sekolah agama, dan ini menciptakan peraturan sekolah yang memaksa siswa untuk melaksanakan aktivitas keagamaan yang tidak relevan dengan prinsip sekolah negeri. Dan umumnya fasilitas yang disediakan untuk kegiatan keagamaan hanya menampung siswa yang berafiliasi dengan keyakinan mayoritas. Permasalahan bahwa sistem mono-religius menyebabkan diskriminasi terhadap minoritas mengenai hak kegiatan keagamaan di sekolah umum. Kesimpulan akan disajikan bersama dengan kritik terhadap dampak pengajaran mono-religius di sekolah negeri. Kata kunci: diskriminasi, mono-religius, Islamisasi, sekolah negeri, Lombok Timur